Основні питання щодо формування і підтримки транзитних потоків в портах України - Котлубай, В.О. (Економічні інновації, 2009)
В статье рассматриваются проблемы и перспективы увеличения объемов переработки транзитных грузов портовой системой Украины. In the article problems and prospects of multiplying the volumes of processing of loads of transits are examined by the port system of Ukraine.